PENGARUH INVESTASI PEMERINTAH, INVESTASI SWASTA, INFLASI, EKSPORT, TENAGA KERJA DAN PRODUKTIVITAS TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (JURNAL ECONOMICA : Research of Economic And Economic Education, 2013)
The research aims to analyze the effect of government investment, private investment, inflation, export, labor, and labor productivity to economic growth in Indonesia. The research finding government investment, private investment, inflation, export, labor, and labor productivity have significant effect to economic growth. The increasing on private investment, lower the inflation rate, the increasing on export will increase the economic growth. It also find labor has no significant effect on economic growth in Indonesia. Private and government investment fluctuation have no effect to economic growth in Indonesia. The study implies to increase economic growth in Indonesia-the government must do development flatten, repair the birocration to create condusive investment environment to attract the investor to Indonesia, ensure economic stabilitation in order to face higher inflation, and improve human resources to increase output and has export value.